EVALUASI PEMERIKSAAN BILIRUBIN TOTAL MENGGUNAKAN MODEL SPECIMEN INSIGNIFICANT DAN MILD HEMOLYSIS: EVALUATION OF TOTAL BILIRUBIN EXAMINATION USING THE INSIGNIFICANT SPECIMEN AND THE MILD HEMOLYSIS MODELS - Kesuma, Suryanata; Rodiyah, Siti; Maulida (POLTEKKES KEMENKES JAYAPURA, 2023)
Bilirubin total merupakan salah satu pemeriksaan fungsi hati. Pemeriksaan bilirubin total umumnya menggunakan sampel darah yang tidak boleh hemolisis, sehingga sampel hemolisis menjadi salah satu faktor yang dapat mempengaruhi hasil pemeriksaan bilirubin total. Hemolisis dapat terjadi secara in vivo dan in vitro. Hemolisis secara in vitro menyebabkan kesalahan pemeriksaan bilirubin total. Tujuan penelitian ini untuk mengetahui hasil evaluasi pemeriksaan bilirubin total menggunakan model specimen insignificant dan mild hemolysis. Metode penelitian ini adalah kuasi eksperimen. Pembuatan hemolisat menggunakan larutan aquadest. Jumlah sampel pada penelitian ini adalah 40 sampel. Pemeriksaan menggunakan metode kolorimetri pada alat fotometer DIRUI DR-7000D. Pemeriksaan hemoglobin digunakan untuk melakukan validasi specimen insignificant dan mild hemolysis. Hasil uji statistik one-way Anova didapatkan nilai Sig < 0.05. Hasil akurasi yang didapatkan adalah -1.83% dan -4.40% < 11.4%, presisi 22.0% dan 20.6% > 7%, TE 38.1% dan 38.5% > 20% TEa berturut-turut sampel insignificant dan mild hemolysis. Kesimpulan terdapat perbedaan secara statistik dan klinis pada hasil evaluasi pemeriksaan bilirubin total model specimen insignificant dan mild hemolysis. Kata kunci: Bilirubin Total, Specimen Insignificant Hemolysis, Specimen Mild Hemolysis The total bilirubin is one of the liver function tests. The entire bilirubin test generally uses blood samples, which are one of the factors that can’t be hemolyzed, so hemolysis samples are one of the factors that can affect the result of the total bilirubin test. Hemolysis can occur in vivo and in vitro. Hemolysis in vitro causes an error in the entire bilirubin test. However, hemolysis specimens are still examined for total bilirubin under certain conditions. The evaluation aims to find out the results of natural bilirubin test specimens insignificant and mild hemolysis. This research method is quasi-experimental. They are making hemolysate using an aquadest solution. The number of samples in this research was 40, and examination was done using the colorimetric method on the DIRUI DR-7000D photometer. A hemoglobin test is used to validate specimens of insignificant and mild hemolysis. The one-way Anova statistical test results obtained a sig value < 0.05. Accuracy results were -1.83% and -4.40% < 11.4%, precision 22.0% and 20.6% > 7%, TE 38.1% and 38.5% > 20% TEa, respectively, samples of insignificant and mild hemolysis. The conclusion: statistical and clinical differences exist in evaluating total bilirubin test results in the tiny and soft hemolysis specimen models. Keywords: Insignificant Hemolysis Specimen, Mild Hemolysis Specimen, Total Bilirubin